A generalization of a theorem of Kühnel on globally defined analytic sets. Issue 11 (2nd November 2021) - Abe, Makoto; Shima, Tadashi; Sugiyama, Shun
Abstract : Let X be a connected K -complete normal complex space. If for every closed discrete set A in X there exists a family F of holomorphic functions on X such that N ( F ) = A, then the K -envelope H ( X ) of holomorphy of X in the sense of Kerner (Math Ann. 1959;138:316–328) coincides with X .